Point-of-Care Ultrasound for Diagnosis of Abscess in Pediatric Skin and Soft Tissue Infections: A Systematic Review and Meta-analysis - Chauhan, Tarun Kumar; Singh, Amar (Journal of Neonatal Surgery, 2025)
Background: Pediatric skin and soft tissue infections (SSTIs) are a frequent cause of emergency visits. The key clinical challenge is differentiating cellulitis from abscess, as abscess requires incision and drainage while cellulitis usually responds to antibiotics. Objective: To evaluate the diagnostic accuracy of point-of-care ultrasound (POCUS) compared with clinical examination in children with SSTIs .Methods: We searched PubMed, Embase, Scopus, and Cochrane (2005–2025). Studies enrolling children (0–18 years) with suspected SSTIs, using POCUS as the index test and incision and drainage, microbiological confirmation, or follow-up as the reference standard were included. QUADAS-2 assessed study quality. A bivariate random-effects model generated pooled sensitivity, specificity, likelihood ratios, and diagnostic odds ratio (DOR). Results: Seven pediatric studies (n = 870) were included. POCUS pooled sensitivity was 90% (95% CI, 82–95%), specificity 80% (95% CI, 72–86%), LR⁺ 4.5, LR⁻ 0.13, DOR 36. The area under HSROC curve was 0.89 (95% CI, 0.86–0.91). Clinical examination alone showed sensitivity 84% and specificity 69%. Subgroup analysis demonstrated higher specificity with trained emergency physicians and high-frequency probes. Publication bias assessment suggested minimal asymmetry. Conclusions: POCUS is a highly sensitive and moderately specific bedside tool for abscess detection in pediatric SSTIs. It outperforms clinical examination and should be integrated into pediatric emergency protocols